Three-Level DTC Based on Fuzzy Logic and Neural Network of Sensorless DSSM Using Extended Kalman Filter - Elakhdar Benyoussef; Abdelkader Meroufel; Said Barkat (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
This paper presents a direct torque control is applied for salient-pole double star synchronous machine without mechanical speed and stator flux linkage sensors. The estimation is performed using the extended Kalman filter known by it is ability to process noisy discrete measurements. Two control approaches using fuzzy logic DTC, and neural network DTC are proposed and compared. The validity of the proposed controls scheme is verified by simulation tests of a double star synchronous machine. The stator flux, torque, and speed are determined and compared in the above techniques. Simulation results presented in this paper highlight the improvements produced by the proposed control method based on the extended Kalman filter under various operation conditions.